Key constraint in construction industry: A review - Nurul Athirah, R.; Doh, S. I. (Penerbit UMP, 2022)
Constraint is a limitation of a situation, agency, or force that obstructs movement toward a goal or purpose. There are several sorts of constraints that might impact building projects. During the early phases of a project, constraints should be recognized and explained in as much detail as possible, so that knowledge of them and their potential impact can be handled. The aim of this study is to identify types of constraints that might occur in the construction industry which may affect the time, cost and scope of the project. The study was carried out on the basis of a literature review with the result and findings of previous researchers. The result and findings from the previous researcher have been analysing in the table together with the method of analysis that being used by them in order to carry out the study. From the review, it can be summarized that the key of constraints can be divided into five major elements. There are Environmental constraints, Legal Constraints, Environmental Constraints, Technical Constraints and Social Constraints. Therefore, by doing this investigation, it will help to give a better solution and performance in term of time, cost and scope of the project by classifying and limiting the constraints in the construction industry especially at an early stage in the project planning and schedule.